Characterization of the efficacy of stent graft treatment in patients with aortic dissection using computational fluid dynamics analysis / Wan Naimah Wan Ab Naim - Wan Naimah, Wan Ab Naim (2018)
Aortic dissection (AD), characterized by separation of the layers of the aortic wall, poses a significant challenge for clinicians. While Stanford Type A AD patients are normally managed using surgical treatment, the optimal treatment strategy for Stanford Type B AD remains controversial. Recently, stent graft treatment for Stanford Type B AD has become more common. The primary aim of placing the stent graft in AD patients is to occlude the primary entry tear so as to restore true lumen (TL) flow and induce false lumen (FL) thrombosis. Even though FL thrombosis indicates a better long term prognosis, many studies have documented that the FL was not completely thrombosed distal to the stent graft. By improving understanding on which group of patients are most likely to benefit from stent graft treatment; a better assessment can be achieved. This project aims to evaluate the progression of Stanford Type B AD after stent grafting using clinical and using computational fluid dynamics (CFD) studies in order to predict the cause of incomplete FL thrombosis. To achieve this aim, analysis of computed tomography angiography (CTA) images for thirteen AD patients who underwent stent graft treatment was performed. The distribution of thrombus was identified, while both diametric and volumetric measurements of the TL and FL at the thoracic and abdominal levels were calculated to investigate their changes after stent graft implantation as well as during the follow-up periods. Next, a preliminary study to predict the formation of thrombus in a Stanford type B AD patient was carried out using CFD. Further extension of the CFD approach was performed to investigate factors leading to the formation of thrombus and aortic remodelling in AD patients implanted with stent grafts using the longitudinal CTA images obtained from five AD patients. In comparison to the dimensional and volumetric measurements, volume measurement was shown to provide supportive information in terms of the morphological changes of aortic dissection after stent grafting repair. Patients with dissection up to the abdominal vicinity, no re-entry tears, and branches partially supplied by the FL at the end of the dissection, were more likely to develop complete FL thrombosis. The morphological results were further supported by the CFD analysis, where patients with more than 80% FL thrombosis had concentrated short distance communications around the abdominal branches, while less than 80% FL thrombosis patients had re-entry tears spreading out along the dissection, which created continuous flow activities inside the FL that disrupted thrombosis. Besides tear distributions, thrombosis was also affected by the number of re-entry tears and the presence of abdominal branches being supplied by the FL. Blood flow inside the FL which affected the formation of thrombus, increased with the number of re-entry tears and when only small amounts of blood that entered the FL exited through the branches. Based on low time-averaged wall shear stress (TAWSS) and high relative residence time (RRT) distributions, all patients showed thrombus formation at the upper FL region, particularly at the vicinity of the closed primary entry tear.